2014
DOI: 10.1080/13546805.2014.973486
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive insight and executive functioning in schizophrenia

Abstract: These results provide support for the hypothesis that executive dysfunctioning is a limiting factor for NI, independently from depressive and anxiety symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…However, investigations of the accuracy of self-reported cognitive functioning in individuals with schizophrenia have predominantly found little correspondence between subjective self-assessments of cognition and objective neuropsychological measures. This is true of both global cognitive abilities (Chang et al, 2015; Ehmann, Goldman, Yager, Xu, & MacEwan, 2007; Johnson, Tabbane, Dellagi, & Kebir, 2011; Keefe, Poe, Walker, Kang, & Harvey, 2006; Poletti et al, 2012; Prouteau et al, 2015; Saperstein, Thysen, & Medalia, 2012) and specific cognitive domains including attention, memory, and executive function (Gilleen, Greenwood, & David, 2011; Medalia & Lim, 2004; Prouteau et al, 2004). Low correspondence of self-report information with neuropsychological performance does not appear to be strongly correlated with positive symptomology (Chang et al, 2015; Medalia & Lim, 2004; Medalia, Thysen, & Freilich, 2008), nor is it restricted to those with lower cognitive performance.…”
Section: Self-reported Cognition In Schizophreniamentioning
confidence: 99%
“…However, investigations of the accuracy of self-reported cognitive functioning in individuals with schizophrenia have predominantly found little correspondence between subjective self-assessments of cognition and objective neuropsychological measures. This is true of both global cognitive abilities (Chang et al, 2015; Ehmann, Goldman, Yager, Xu, & MacEwan, 2007; Johnson, Tabbane, Dellagi, & Kebir, 2011; Keefe, Poe, Walker, Kang, & Harvey, 2006; Poletti et al, 2012; Prouteau et al, 2015; Saperstein, Thysen, & Medalia, 2012) and specific cognitive domains including attention, memory, and executive function (Gilleen, Greenwood, & David, 2011; Medalia & Lim, 2004; Prouteau et al, 2004). Low correspondence of self-report information with neuropsychological performance does not appear to be strongly correlated with positive symptomology (Chang et al, 2015; Medalia & Lim, 2004; Medalia, Thysen, & Freilich, 2008), nor is it restricted to those with lower cognitive performance.…”
Section: Self-reported Cognition In Schizophreniamentioning
confidence: 99%
“…Of all 12 papers in this review that examined the relationship between self-assessment and depression, only 3 [22,24,35] failed to find any significant relationship.…”
Section: Predictors Of Self-report Concordancementioning
confidence: 82%
“…Prouteau et al [22] split participants with schizophrenia into two subgroups based on their performance on the Trail Making Test (TMT): a subgroup identified as "executively normal" and a "dysexecutive" subgroup. Researchers then calculated discrepancy scores using the SSTICS and performance on the Modified Card Sorting Test (MCST) to represent neurocognitive insight and compared the two subgroups to each other and a control group.…”
Section: Self-reported Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that levels of depressive symptoms and cognitive performance are crucial signals determining the accuracy and direction (underestimation or overestimation) of patients’ subjective self-reported evaluations of their own cognitive impairments. Furthermore, it has been suggested that weakened executive function [ 11 , 12 ] and autistic traits [ 13 ] are also determinants of IA impairment. To date, the problem of self-assessment in patients with schizophrenia has been investigated by comparing the patient's self-rating with informant-rating (high-contact clinician or case manager, or patient’s family member) or using correlations between self-rating and performance of objective neuropsychological tests [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%